Percutaneous Cecostomy Catheters - Akinduro, Oluwanifemi G.; Jacobs, Adam P.; Gunn, Andrew J. (Seminars in Interventional Radiology, 2025)
Percutaneous cecostomy catheters can be placed in the setting of either fecal incontinence or large bowel obstruction. While there are several etiologies for these disorders, the purpose of the cecostomy catheter is to provide ease of access for antegrade enemas in patients with fecal incontinence or relieve pain and discomfort in patients with a large bowel obstruction. Image-guided, percutaneous catheter placement into the cecum fits easily into the skillset of the interventional radiologist. Even though the literature consists of mostly single-center, retrospective case series, the procedure shows high rates of technical success, outstanding clinical outcomes, excellent patient satisfaction scores, and low rates of major adverse events. The purpose of this article is to review indications for cecostomy catheter placement, outline preprocedural patient evaluation, describe intraprocedural steps of catheter placement, detail postprocedural follow-up, and review both technical and clinical outcomes of cecostomy catheter placement.
Keywords: cecostomy; catheters; antegrade enemas